Pendidikan Multikultural Dalam Pembelajaran Agama Islam di Sekolah Menegah Atas Negeri (SMAN) 1 Kendawangan Kabupaten Ketapang - sukino, Arief sukino; Oktariansyah, Oktariansyah; Erwin, Erwin (Literasi: Jurnal Ilmu Pendidikan, 2020)
AbstractSenior High School (SMA) is a strategic educational environment in shaping the personality of multicultural students. Through Islamic Religious Education the strategic role of the school is becoming increasingly apparent because Islamic Education that is carried out properly will bring a positive and productive attitude change. The purpose of this study is to investigate multicultural education in SMAN 1 Kendawangan, which is with a lot of diversity. The method used is descriptive qualitative with a phenomenological approach. The results of this study indicate that the first important argumentation of multicultural Islamic religious education in Islamic religious education is the factor, religious religions of ethics, cultural customs, and social status that are often the latent potential of social conflict. Second Multicultural education is carried out by internalizing in an integrated manner through contextualization and Extention of the material, the need for learning strategies, and attitude/behavior-based assessments. Third multicultural education is carried out by incidental (temporary) actions, namely by counseling during the flag ceremony, conducting Friday blessings (healthy and clean schools), and developing tolerance through the momentum of religious holidays in schools.Keywords: Multicultural, Islamic Religious Education, Kendawangan AbstrakSekolah menegah Atas SMA adalah lingkungan Pendidikan yang setrategis dalam pembentukan kepribadian siswa multikuturalis. Melalui Pendidikan Agama Islam peran strategis sekolah tersebut menjadi semakin nyata, karena Pendidikan Agama Islam yang dilaksanakan dengan baik akan membawa perubahan sikap positif dan produktif. Tujuan penelitian ini adalah untuk menginvestigasi Pendidikan multicultural di SMAN 1 Kendawangan, yang merupakan dengan banyak keragaman. Metode yang digunakan adalah deskriptif kualitatif dengan pendekatan fenomenologi. Hasil penelitian ini menunjukkan bahwa pertama argumentasi pentinga Pendidikan agama Islam multicultural dalam Pendidikan agama Islam adalah factor, keragama sgama etis, adat budaya dan status social yang sering menjadi potensi laten konflik social. Kedua Pendidikan mulitkultural dilakukan dengan menginternalisasikan secara terintegrasi melalui kontekstualisasi dan mepengangan materi, perluasa strategi pembelajaran dan penilaian berbasis sikap/perilaku. Ketiga pendidkan multikultur dilasakukan dengan tindakan insidental (temporary) yakni dengan penasihatan pada saat upacara bendera, melakukan jumat berkah (sekolah sehat dan bersih) dan pengembangan toleransi melalui momentum hari besar keagamaan di sekolah.Kata kunci: Multikultural, Pendidikan Agama Islam, Kendawangan